A prospective, randomized, cross sectional study of manual versus vacuum extraction of mobile head in caesarean section - A., Bhagyashree; Thomas, Julie; Gudi, Shobha N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Considering the high rate of caesarean section, and the difficulty during delivery of the floating foetal head even by the most experienced obstetrician, the use of vacuum has been described. The present study was undertaken with the hypothesis that, vacuum assisted foetal head delivery during caesarean section is safe and effective without increasing maternal and neonatal complications. The outcomes enumerated by the limited literature available need to be evaluated before it is used routinely. Methods: A prospective, randomized, comparative, cross sectional Hospital based study was conducted at St. Philomena’s Hospital, Bangalore. Every woman randomized for the study received either conventional method or ventouse extraction of fetal head at cesarean section. 200 women were enrolled into the study with 100 in each arm. The primary outcome measures were percentage of successful extractions and I-D interval. The secondary outcome measures were, uterine incision extension, estimated blood loss, Apgar scores, neonatal hyperbilirubinemia and neonatal scalp or head injury. Results: Successful extraction was done in 89 % and 98 % cases in manual and vacuum extraction cases. (p =0.0184). U-D interval in the manual extraction group was 66.59±4.64 seconds and in the Vacuum extraction group it was 56.06±3.46 seconds (P<0.001). The mean pre-delivery hemoglobin levels in group I was 11.6±0.73 compared to 11.36±0.49 gm% in group II. The mean post-delivery hemoglobin levels in group I was 10.29±0.79 compared to 10.21±0.53 gm% in group II (p <0.001). The uterine incision extensions were significantly higher in manual extraction group, 18 of the 100 women (18 %), whereas only 2 of the 100 women in vacuum group had uterine extensions (p=0.0002). Conclusions: Authors conclude that the routine use of ventouse is safe and effective for mobile fetal head extraction at cesarean section.